HIDDEN HEALTHCARE-ASSOCIATED INFECTION BURDEN IN UROLOGY DEPARTMENTS AND THE RATIONALE FOR AN AI-SUPPORTED INTEGRATED EPIDEMIOLOGICAL MONITORING MODEL - Khamzayeva Nilufar Toshtemirovna; Saidkasimova Nargiza Sayfullayevna; Kurbaniyazova Malika Oralbayevna; Mavlyanov Jaloliddin Abduvakhobovich (The Conference Hub, 2026)
Urology departments are high-risk settings for healthcare-associated infections (HAIs) due to invasive procedures, catheterization, and intensive antibiotic use. However, official reports of the Committee for Sanitary-Epidemiological Welfare and Public Health (CSEWPH) in Olmazor District registered zero HAIs in urology units during 2023–2024, suggesting possible under-detection. This study analyzed microbiological, environmental, and clinical indicators to assess the hidden infection burden. Laboratory data demonstrated persistently high biomaterial positivity (57.0–58.6%), accompanied by a significant shift toward nosocomial pathogens, including Klebsiella pneumoniae and Candida spp. Environmental monitoring revealed a sharp increase in surface contamination in 2025, including aseptic zones, indicating a critical epidemiological signal. Prolonged antibiotic use was common, potentially exceeding prophylactic recommendations. These findings support the presence of a hidden HAI burden and justify the implementation of an integrated AI-supported, signal-based epidemiological monitoring system to enhance early detection and targeted infection prevention.
Keywords: Healthcare-associated infections, urology departments, hidden infection burden, microbiological surveillance, environmental contamination, antibiotic stewardship,